Skin Displacement as fascia tissue manipulation at the lower back affects instantaneously the flexion-and extension spine, pelvis, and hip range of motion - van Amstel, Robbert N.; Jaspers, Richard T.; Pool-Goudzwaard, Annelies L. (Frontiers in Physiology, 2022)
Low back pain (LBP), associated with spine, pelvis, and hip mobility impairments can be caused by tight muscle contractions, to protect sensitized lumbar fasciae. Fascia tissue manipulations are used to treat lumbar fascia in LBP. The effect of fascia tissue manipulations through lumbodorsal skin displacement (SKD) on mobility is inconclusive likely depending on the location and displacement direction of the manipulation. This study aimed to assess whether lumbodorsal (SKD) affects the flexion -and extension range of motion (ROM), in healthy subjects. Furthermore, to test the effect of SKD at different locations and directions. Finally, to assess intertester and intratester reliability of SKD.